Clinicopathological features in two families with MARS‐related Charcot–Marie–Tooth disease. Issue 6 (20th June 2022) - Ma, Zhixing; Lv, He; Zhang, Hongwei; Wang, Hui; Li, Jingcheng; Yu, Meng; Zhu, Ying; Huang, Diandian; Meng, Lingchao; Yuan, Yun
Abstract : Mutations in MARS gene cause dominant Charcot–Marie–Tooth disease (CMT) 2U. The aim of this study is to investigate phenotypic heterogeneities and peripheral neuropathology of MARS ‐related CMT patients. We identified a heterozygous p. R199Q mutation and an already reported heterozygous p. P800T mutation of MARS gene in two unrelated families using targeted next‐generation sequencing. The first pedigree comprised three patients over three generations and the second pedigree comprised two patients over two generations. In addition of an asymptomatic carrier in the second pedigree, all patients presented with childhood‐onset length dependent sensorimotor neuropathy with pes cavus. Nerve conduction studies revealed slowing of motor nerve conduction velocities (MNCV) of the median nerve indicating intermediate neuropathy in the patient with the p. R199Q mutation, and normal MNCV with reduced compound muscle action potential indicating axonal neuropathy in the patient with the p. P800T mutation. Magnetic resonance imaging detected a pattern of nerve changes similar to those in demyelinating polyneuropathies in intermediate type (p. R199Q mutation) patients compared with normal in the axonal type (p. P800T mutation) patients. Additionally, sural nerve biopsy revealed loss of myelinated axons with onion bulb formation in both mutations. By electron microscopy, a marked decrease of myelinated and unmyelinated fiber, neurofilaments aggregate with degenerating mitochondria and microtubule loss in axons were frequently found. Denervated Schwann cell complexes and few collagen pockets indicated involvement of unmyelinated Schwann cells. Therefore, the investigated MARS mutations cause not only the known axonal type but also intermediate type neuropathy with involvement of both axons and Schwann cells. Those findings are useful for the differential diagnosis of CMT patients with unknown MARS variants.